Fine-mapping of a major QTL controlling angular leaf spot resistance in common bean (Phaseolus vulgaris L.) - Keller, Beat; Manzanares, Chloe; Jara, Carlos E.; Lobaton, Juan David; Studer, Bruno; Raatz, Bodo (Springer, 2015)
A major QTL for angular leaf spot resistance in the common bean accession G5686 was fine-mapped to a region containing 36 candidate genes. Markers have been developed for marker-assisted selection. Common bean (Phaseolus vulgaris L.) is an important grain legume and an essential protein source for human nutrition in developing countries. Angular leaf spot (ALS) caused by the pathogen Pseudocercospora griseola (Sacc.) Crous and U. Braun is responsible for severe yield losses of up to 80 %. Breeding for resistant cultivars is the most ecological and economical means to control ALS and is particularly important for yield stability in low-input agriculture. Here, we report on a fine-mapping approach of a major quantitative trait locus (QTL) ALS4.1GS, UC for ALS resistance in a mapping population derived from the resistant genotype G5686 and the susceptible cultivar Sprite. 180 F3 individuals of the mapping population were evaluated for ALS resistance and genotyped with 22 markers distributed over 11 genome regions colocating with previously reported QTL for ALS resistance. Multiple QTL analysis identified three QTL regions, including one major QTL on chromosome Pv04 at 43.7 Mbp explaining over 75 % of the observed variation for ALS resistance. Additional evaluation of 153 F4, 89 BC1F2 and 139 F4/F5/BC1F3 descendants with markers in the region of the major QTL delimited the region to 418 kbp harboring 36 candidate genes. Among these, 11 serine/threonine protein kinases arranged in a repetitive array constitute promising candidate genes for controlling ALS resistance. Single nucleotide polymorphism markers cosegregating with the major QTL for ALS resistance have been developed and constitute the basis for marker-assisted introgression of ALS resistance into advanced breeding germplasm of common bean.